Isolation and identification of tannin-degrading bacteria from goat feces, ruminal fluid, and rumen gut - Muhammad Syafiq Suhaimi,; Fayyadhah Asyiqin Zailani,; Nur Farah Syuhada Mohd Zaki,; Farizan Aris,; Mohd Taufiq Mat Jalil,; Nurul Aili Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tannins are toxic polyphenols present in various plants, contributing to microbial attacks and plant protection due to their astringence and bitter taste. However, high tannin inclusion in poultry diets will result in dyspepsia, hampering nutrient absorption and digestion. Interestingly, several bacteria occupying the rumen and gastrointestinal tract (GIT) of animals may tolerate tannins and degrade them by wielding tannase enzymes. The study aims to isolate and characterize potential tannin-degrading bacteria (TDB) from several ruminant specimens. The TDBs were isolated based on their tannin hydrolyzing ability on a minimal salt medium (MSM) agar complemented with 0.2% tannic acid as the sole source of carbon and energy. The maximum tannin tolerance of the isolates was characterized using increased tannin concentrations on the MSM agar plates. Furthermore, the tannase activity was also evaluated over a five-day incubation. A total of 42 tannin degraders were isolated, and 10 TDBs were chosen for further characterization based on the hydrolyzed zone produced. Molecular identification revealed the presence of Bacillus cereus (TDB536), Lysinibacillus macroides (TDB17), Acinetobacter nosocomialis (TDB18, 20, 23, 24, 30, 35), and Staphylococcus saprophyticus (TDB40). TDB17, TDB18, and TDB24 showed the highest tannic acid tolerance at 1.0%, while TDB36 and TDB40 exhibited the lowest tolerance at 0.4%. Each TDB displayed varying tannase activities, ranging from 11.56 to 42.08 U/mL over a five-day incubation period. TDB5 and TDB35 demonstrated significantly higher tannase activity on day 2 (p<0.05). Meanwhile, TDB23 and TDB24 showed the highest tannase on day 4 (p<0.05). Among the isolates, A. nosocomialis strain AE6 (TDB24) from feces exhibited the highest tannase activity (42.08 U/mL) and represented the best TDB. The isolated strains demonstrate their capabilities in reducing tannin's antinutritional effects in poultry feed.